2012
DOI: 10.2478/v10216-011-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stubble Heights and Treatment Duration Time on the Performance of Water Dropwort Floating Treatment Wetlands (FTWS)

Abstract: in the first 4 days, but significant difference was detected after day 4. The optimum treatment duration time for the FTWs with Water Dropwort will depend on the nutrients to be removed. These results will provide basis for further application of the FTWs at large scale, as well as for future studies on the mechanism of nutrient removal process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The decrease in the secretion of organic matter by roots, which could be inferred from the decrease in the aboveground length and biomass of the plants in our study, may exacerbate the decrease in winter. However, due to (1) the increase in root surface area (inferred from the slight increase in root length and biomass in the winter batches relative to the late autumn batches), (2) the maintenance of root activity (demonstrated by both our results and other studies27 and (3) the possible presence of psychrotrophic bacteria7, N removal via the microbial pathway decreased only 24.53% in the winter batches compared to the late autumn batches. Moreover, another factor also contributes to the relatively high N and P removal efficiencies in winter in the FW-M system with overwintering macrophytes: a slight increase in the N removal efficiency of the deposition storage pathway is induced by the slight increase in Oenanthe clecumbens roots.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…The decrease in the secretion of organic matter by roots, which could be inferred from the decrease in the aboveground length and biomass of the plants in our study, may exacerbate the decrease in winter. However, due to (1) the increase in root surface area (inferred from the slight increase in root length and biomass in the winter batches relative to the late autumn batches), (2) the maintenance of root activity (demonstrated by both our results and other studies27 and (3) the possible presence of psychrotrophic bacteria7, N removal via the microbial pathway decreased only 24.53% in the winter batches compared to the late autumn batches. Moreover, another factor also contributes to the relatively high N and P removal efficiencies in winter in the FW-M system with overwintering macrophytes: a slight increase in the N removal efficiency of the deposition storage pathway is induced by the slight increase in Oenanthe clecumbens roots.…”
Section: Discussionsupporting
confidence: 39%
“…Additionally, the slow winter growth of the roots indicates that the roots maintain a relatively high degree of activity and purification abilities throughout the winter12. The species Oenanthe clecumbens studied in this paper probably meets these requirements because most of its leaves remain active and its roots continue to grow, thereby improving the contaminant removal rates in winter12 and resuming rapid growth in the early spring27. Our result, FE am values ranging from 15.23% to 25.86% for N and P, confirmed this inference (We can infer the performance of warm-season plant CFW in winter according to the treatment of floating mats without plants because most warm-season plants in CFW can’t survive winter at our study area).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5. Xin et al, [18] reported that in aquatic system, the "carbonate system" which is typically be similar to carbonic acid, carbon dioxide, hydrogen ion and bicarbonate, carbonate are the most significant acid-base interactions. Carbon dioxide in the tank 1 decreased during the photosynthesis process where microalga uptake and this cause shift in carbonate system in an alkaline direction.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that floating wetland can act as a buffer to the pH conditions in the water body. They influence the water body's aciditybase and allows the conditions to remain steady around neutral conditions [18]. It also suggested that the pH condition is not relies on the water temperature.…”
Section: Resultsmentioning
confidence: 99%